PENGATURAN KOMISI PENGAWAS PERSAINGAN USAHA DALAM PERATURAN PRESIDEN REPUBLIK INDONESIA NOMOR 100 TAHUN 2024 - I Wayan Suka Antara Yasa; I Ketut Bakuh (Fakultas Hukum Universitas Ngurah Rai, 2026)
KPPU is a special organ that has a double duty in addition to creating order in business competition also plays a role in creating and maintaining a conducive business competition climate. In its development, the KPPU's legal arrangements have changed in line with existing business developments. The purpose of writing this scientific journal is to better understand the latest regulation of the Business Competition Supervisory Commission (KPPU) in Presidential Regulation of the Republic of Indonesia Number 100 of 2024. The research method used in this research is normative research method with statutory approach and conceptual approach. The result of this study is the urgency of changing the regulation of the Business Competition Supervisory Commission (KPPU) to support the optimization and effectiveness of the implementation of duties and functions in the field of business competition supervision and supervision of partnership implementation, on the other hand, the laws and regulations governing KPPU are no longer in accordance with the needs and dynamics of the organization and legal developments. The position, duties and functions of the Business Competition Supervisory Commission (KPPU) have been regulated sequentially in Article 1 to Article 3 of Presidential Regulation No. 100 of 2024 concerning the Business Competition Supervisory Commission.